Keandalan Sistem Jaringan Distribusi 20 Kv Penyulang Tk-06 Berdasarkan Saidi- Saifi Di PT PLN (Persero) Ulp Medan Baru: TK 06 Feeder of Distribution Network System Reliability Based on Saidi – Saifi at Costumer Service Unit of PT PLN (Persero) Medan Baru - Andika Ambarita, Roy Putra; Suparmono; Sembiring, Martin (Jurnal Ilmiah Tenaga Listrik, 2023)
AbstractReliability of the electric power system is a very important factor for PT PLN (Persero). As the population increases, the demand for quality electrical energy distribution must increase and become more reliable. In improving the quality of distribution system distribution, namely calculating the reliability index based on average interruption frequency (SAIFI) and average interruption duration (SAIDI). By analyzing the reliability of this distribution system, it can be seen whether the reliability of the TK-06 feeder is in accordance with applicable standards. The SAIDI-SAIFI value calculation method used is a manual calculation method using mathematical formulas. The level of reliability of the TK-06 Feeder distribution network system is said to be reliable in accordance with SPLN 68-2: 1986. Blackouts often occur due to disruption or maintenance. The potential loss of income due to blackouts in the distribution network of PT PLN (Persero) ULP Medan Baru is Rp 316,545,783. Abstrak Keandalan sistem tenaga listrik merupakan faktor yang sangat penting bagi PT PLN (Persero). Seiring dengan bertambahnya jumlah penduduk, maka permintaan penyaluran kualitas energi listrik harus semakin meningkat dan semakin andal. Dalam peningkatan kualitas penyaluran sistem distribusi yaitu perhitungan indeks keandalan berdasarkan frekuensi gangguan rata-rata SAIFI dan lama gangguan rata-rata SAIDI. Adanya analisa keandalan sistem distribusi ini, dapat diketahui keandalan pada penyulang TK-06 apakah sudah sesuai dengan standar yang berlaku. Adapun metode perhitungan nilai SAIDI-SAIFI yang digunakan adalah metode perhitungan manual dengan rumus-rumus matematis. Tingkat keandalan sistem jaringan distribusi Penyulang TK-06 dikatakan andal sesuai dengan SPLN 68-2 1986. Pemadaman sering terjadi diakibatkan oleh adanya gangguan maupun pemeliharaan. Adapun potensi kehilangan pendapatan akibat pemadaman pada jaringan distribusi PT PLN (Persero) ULP Medan Baru sebesar  Rp 316.545.783.